Firm Profitability and Carbon Disclosure: The Moderating Effect of Firm Size - Mukti Trio Putra; Intan Zoraya; Berto Usman (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates the relationship between firm profitability, measured by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), and carbon disclosure among publicly listed companies in Indonesia, while also examining how firm size influences this relationship. Methodology/approach: This study utilizing panel data and multiple regression with a sample of 47 firms from 2018 to 2022. Results/findings: The results reveal that profitability does not have a significant direct effect on carbon disclosure. However, firm size significantly moderates the relationship between ROA and carbon disclosure, indicating that larger firms face greater scrutiny and are more likely to disclose carbon emissions as part of their legitimacy strategies. Conclusions: The study concludes that carbon disclosure practices are primarily shaped by external legitimacy pressures, particularly in larger firms, rather than profitability. Inadequate regulatory mandates and limited standardization hinder transparency, underscoring the critical importance of governmental regulation and societal oversight in fostering accountability. Limitations: This study is limited by its reliance on legitimacy theory, simplified models without control variables, an item-based disclosure measure, exclusive focus on Indonesian listed firms, and a restricted five-year observation period, constraining generalizability and explanatory power. Contributions: The study contributes by reinforcing legitimacy theory in explaining carbon disclosure, extending insights on firm size’s moderating role, and emphasizing that disclosure is shaped more by external pressures than profitability, offering managerial guidance on transparency amid limited regulation.